The Interaction of the Factor Vlll/von Willebrand Factor Complex with Hematin - Green, David; Furby, Fiona H; Berndt, Michael C (Thrombosis and Haemostasis, 1986)
Intravenous infusion of hematin, used in the treatment of acute porphyria, induces a decline in the plasma factor VIH/von Willebrand factor complex (VIII/vWF) and thrombocytopenia. We investigated this problem by studying the interaction between hematin, purified VIII/vWF, and platelets in vitro. Hematin was labeled with either 59Fe or 3H and characterized by gel chromatography. Hematin self-aggregated, forming a complex with an average molecular weight of approximately 10,000 daltons. When incubated with VIII/vWF for 30 min at 37° C and applied to Sepharose CL-4B, the hematin eluted with the VIII/vWF in the void volume. Hematin inhibited the dissociation of factor VIII antigen (VIII :Ag) from the von Willebrand antigen (vWF:Ag) in 0.25 M CaCl2, and reversed the aggregation of VIII:Ag induced by 0.1 M 6-aminocaproic acid. Both hematin and the hematin-VIII/vWF complex bound to washed normal platelets and to platelets from a patient with Bemard-Soulier syndrome. Thromb-asthenic platelets were not aggregatable by hematin, and bound significantly less hematin-VIII/vWF than normal platelets suggesting that hematin-induced platelet activation was required for binding. Likewise, binding was inhibited by PGE1 which also prevented aggregation. We conclude that hematin forms complexes with VIII/vWF, alters the functional activity and dissociation of this compound, and participates in the binding of VIII/vWF to platelets.
Keywords: Factor VIII/vWF; Hematin; Platelets; Porphyria